Impact of alpha-damage and helium production on the heat capacity of actinide oxides - Wiss, Thierry; Konings, Rudy J. M.; Staicu, Dragos; Benedetti, Alessandro; Colle, Jean-Yves; Rondinella, Vincenzo V.; Maugeri, Emilio; Talip, Zeynep; Janssen, Arne; Dieste, Oliver; Cognini, Luana; De Bona, Emanuele; et al. (Frontiers in Nuclear Engineering, 2025)
The heat capacity of alpha-damaged uranium, plutonium, and americium mixed dioxide (Uu, Puv, Amw)O2±x samples was measured during thermal annealing. The excess of heat released was assessed and the recovery stages associated with various defects described by integrating results from transmission electron microscopy, helium desorption spectroscopy, thermal diffusivity, and XRD annealing studies. It is shown that different defect-annealing stages could be singled out. It could also be evidenced that the excess of energy stored in defects tends to saturate after rather low damage levels, but that, with increasing radiogenic helium production, another contribution of stored energy appears which can be attributed to the formation of He-defect complexes that cannot be annihilated until higher temperatures are reached.